Multiple frequency microstrip five-port ring junction circuit for six-port reflectometer (SPR) - Baharuddin, Siti Aishah; Cheng, Ee Meng; A. Rahim @ Samsuddin, Hasliza; Lee, Kim Yee; Abbas, Zulkifly; Mohd Nasir, Nashrul Fazli; Lee, Y. S. (2017)
The interest of the portable microwave instrument system has grown rapidly in recent years. Thus, Six-Port Reflectometer (SPR) is proposed. SPR provides a simple and inexpensive solution to industrial need of network analyzer. This paper presents the design of the multiple frequencies microstrip Five-Port ring junction which has operating frequencies of 0.37 GHz, 1.40 GHz, 2.10 GHz, 3.10 GHz and 3.80 GHz. The simulation result exhibit optimum specifications and less mismatch error.